Medieval Damascus : plurality and diversity in an Arabic library : the Ashrafiya library catalogue - Hirschler, Konrad (Edinburgh studies in classical Islamic history and culture., 2016)
The written text was a pervasive feature of cultural practices in the medieval Middle East. At the heart of book circulation stood libraries that experienced a rapid expansion from the twelfth century onwards. While the existence of these libraries is well known, our knowledge of their content and structure has been very limited as hardly any medieval Arabic catalogues have been preserved. This book discusses the largest and earliest medieval library of the Middle East for which we have documentation - the Ashrafiya library in the very centre of Damascus - and edits its catalogue. The catalogue shows that even book collections attached to Sunni religious institutions could hold very diverse titles, including Mutazilite theology, Shiite prayers, medical handbooks, manuals for traders, stories from the 1001 Nights, and texts extolling wine consumption. At the same time this library catalogue decisively expands our knowledge of how books were thematically and spatially organised on the shelves of such a large medieval library. Listing over two thousand books the Ashrafiya catalogue is essential reading for anybody interested in the cultural and intellectual history of Arabic societies. Setting it into a comparative perspective with contemporaneous libraries on the British Isles opens new perspectives for the study of medieval libraries. Key features: includes an annotated translation of the Ashrafiya catalogue and full-colour facsimile reproduction of the catalogue's unique manuscript; seeing which books were held in the library give insights into text circulation and medieval 'bestsellers'; the publication of the catalogue provides the first documentary material for comparative research with libraries in other world regions; the organisation of the catalogue contributes to the discussion on how practitioners created systems and hierarchies of scholarly fields of knowledge.